Understanding Network File Systems (NFS): Architecture, Variations, and Implementation - Mohan Babu Talluri Durvasulu, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Network File System (NFS) represents a critical technology in distributed computing, evolving significantly since its inception by Sun Microsystems. This comprehensive article explores the architectural framework, performance characteristics, and implementation strategies of NFS across various protocol versions and enterprise environments. The article delves into technical considerations including network optimization, security mechanisms, and storage efficiency, highlighting how modern NFS implementations deliver robust, scalable, and secure distributed storage solutions that meet the complex demands of contemporary computing infrastructures.
Keywords: Authentication; Caching; Network File System; Performance; Storage